Controlling Noise Levels on the Hearing Health of Mining Workers in the Crushing Plant Area - Ahmad Ikhsan; Mulya Gusman; Eri Barlian; Nurhasan Syah; Muhamad Sholichin (Postgraduate, University of Mataram, 2025)
The mining industry, especially in the crushing plant area, faces serious problems related to noise that can reach more than 85 dB(A). Noise exposure for 8 working hours is at risk of causing temporary or permanent hearing loss (NIHL), which is a common occupational disease found in crushing plant workers. The type of research used in this study is descriptive analytical with a cross-sectional approach. Data collection techniques were carried out by measuring noise levels in the Crushing Plant area and distributing questionnaires to obtain data on the hearing health of mining workers. The location of this study was at CV. Tekad Jaya. The results of the noise level study at CV. Tekad Jaya showed an alarming situation, where 50% of the 14 measurement points exceeded the threshold of 85 dB, with a peak of 96.86 dB at point Std 10. The health impacts were clearly visible with 46.2% of workers experiencing headaches and 61.5% having difficulty communicating, even though the majority had used PPE. The combination of distance and vegetation has proven effective in reducing noise up to 76 dBA at a distance of 95 meters. The metal plate enclosure system showed positive results, reducing noise levels to 83 dBA inside and 67 dBA outside the building. Recommended control strategies include a zoning system with double protection, worker rotation, and health monitoring for areas >85 dBA, and a preventive approach for zones <85 dBA.